The Impact of COVID-19 on Healthy Related Issues, A structured Review - Al-Hamamy, Hiyam Rauof (AL-Kindy College Medical Journal, 2021)
Coronavirus: (COVID-19) is a recently discovered viral disease caused by a new strain of coronavirus.The majority of patients with corona-virus infections will have a mild-moderate respiratory disease that recovers without special care. Most often, the elderly, and others with chronic medical conditions such as asthma, coronary disease, respiratory illness, and malignancy are seriously ill.    COVID-19 is spread mostly by salivary droplets or nasal secretions when an infected person coughs or sneezes.    COVID-19 causes severe acute respiratory illness (SARS-COV-2). The first incidence was recorded in Wuhan, China, in 2019.  Since then it spreads leading to a pandemic.The typical incubation time for COVID-19 infection is 2-14 days (normally 5). The common features include fever, cough, tiredness, difficulty in breathing, loss of smell or taste. Occasionally, signs are absent. COVID-19 complications include renal failure, syndrome of cytokine release, pneumonia, respiratory failure, lung fibrosis.